Qualitative research in nursing and healthcare - Holloway, Immy; Holloway, Immy; Wheeler, Stephanie (Wiley-Blackwell, 2010)
Incorporates the developments in nursing research. This book looks at initial stages, methods of data collection, qualitative approaches and analysis of collected data. It considers a variety of approaches from ethnography to action research. It links research with real nursing practice through relevant examples.